2006
DOI: 10.1002/anie.200600938
|View full text |Cite
|
Sign up to set email alerts
|

2D NMR Spectroscopic Evidence for Unprecedented Interactions of cis‐[Rh2(dap)(μ‐O2CCH3)21‐O2CCH3)(CH3OH)](O2CCH3) with a DNA Oligonucleotide: Combination of Intercalative and Coordinative Binding

Abstract: Slip it in: The dual capability of intercalation and coordination binding of dirhodium complexes was observed in the reaction of the title complex with d(CTCTCAACTTCC). A major adduct with the 1,12‐diazaperylene (dap) group intercalated between the A6 and A7 residues was produced. Additionally, the Rh atom that is not bound to the dap group forms a coordinative bond to the N7 site of A6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…This trend was also apparent in the Δδ = +0.14 ppm value reported for cis -[Rh 2 (dap)(μ-O 2 CCH 3 )(η 1 -O 2 CCH 3 )(CH 3 OH)] + that covalently binds at the A 6 position of d(CTCTCAACTTCC)•d(GGAAGTTGAGAG) while also intercalating between the A 6 and A 7 nucleotides. 42 …”
Section: Resultsmentioning
confidence: 99%
“…This trend was also apparent in the Δδ = +0.14 ppm value reported for cis -[Rh 2 (dap)(μ-O 2 CCH 3 )(η 1 -O 2 CCH 3 )(CH 3 OH)] + that covalently binds at the A 6 position of d(CTCTCAACTTCC)•d(GGAAGTTGAGAG) while also intercalating between the A 6 and A 7 nucleotides. 42 …”
Section: Resultsmentioning
confidence: 99%
“…Among the first reports dealing with the anticancer properties of Rh(III) compounds were those investigating the salt reported by Sheldrick and co-workers [18][19][20][21]. Another very interesting concept involving dirhodium(II,II) complexes that preferentially bind to the nucleobases of RNA and DNA, thereby disrupting protein synthesis and cell proliferation, has been developed by Dunbar and co-workers [22][23][24]. Their research showed that the exchange of photo-labile acetonitrile ligands coordinated to the oxypyridine-bridged dirhodium core by aqua ligands could be significantly accelerated upon light irradiation and was also accompanied by a 16-fold increase in cytotoxicity.…”
Section: Trans-[tetrachloridobis(1h-indazole)ruthenate(iii)])mentioning
confidence: 99%
“…Recently, we described the synthesis of a wide range of diazaperylenes as large‐surface ligands with increased π‐delocalization and the corresponding flexible nonplanar bisisoquinolines . These ligands are intensely studied chelating ligands in the coordination chemistry of transition metal ions . Complex formation and stability of the ligands 1 to 12 (Scheme A) with various types of transition metal ions in the gas phase has been studied by us using ESI‐MS and collision‐induced dissociation (CID) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 These ligands are intensely studied chelating ligands in the coordination chemistry of transition metal ions. [23][24][25] Complex formation and stability of the ligands 1 to 12 (Scheme 1A) with various types of transition metal ions in the gas phase has been studied by us using ESI-MS and collision-induced dissociation (CID) measurements. The homoleptic [1:1] and [1:2] silver (1) complexes of ligands 1 and 2 had been investigated earlier.…”
Section: Introductionmentioning
confidence: 99%